Drowning Risk Analysis Comparing Surf Bather Subgroups - Damian Morgan; Joan Ozanne-Smith (Applied Sciences, 2021)
The study assessed the utility of risk analysis for advancing knowledge on drowning risk factors. The setting was unintentional drowning of surf bathers in Australia. Bathers reported earlier exposure to selected risk factors (swimming ability, wave height associated with rip currents and surf bathing experience) and were observed for water exposure (in minutes). These data were then assembled in mathematical models. The analysis forecast relative drowning risk pertaining to risk markers representing selected surf bather subgroups (gender, age and water activity). Contextualized through previous study findings, comparison of results with a gold standard obtained from mortality data generated new surf bather drowning hypotheses suitable for future testing by rigorous analytical epidemiologic designs. The hypotheses were: (1) The male to female comparative surf bather drowning rate is explained primarily by differences in crude water exposure; (2) the association of cardio-vascular medical conditions with surf bather drowning is stronger for older surf bathers compared to younger surf bathers; and (3) other risk contributors to surf bather drowning are: Poorly calibrated perception of bathing ability (overconfidence) and use of alcohol. Nonetheless, drowning rates appear generally consistent with time exposure to water. The study findings may also support drowning prevention strategies targeting risk marker subgroups.